Tuning and switching effects of quasi-BIC states combining phase change materials with all-dielectric metasurfaces - Barreda, Angela; Zou, Chengjun; Sinelnik, Artem; Menshikov, Evgenii; Sinev, Ivan; Pertsch, Thomas; Staude, Isabelle (Optical Materials Express, 2022)
Emission enhancement of quantum emitters is particularly relevant in the development of single-photon sources, which are key elements in quantum information and quantum communications. All-dielectric metasurfaces offer a route towards strong enhancement of local density of optical states via engineering of high quality factor optical modes. In particular, the recently proposed concept of quasi-bound states in the continuum (quasi-BIC) allows for precise control of such resonances in lattices with an asymmetric unit cell. Still, the spectral band of emission enhancement is usually fixed by the geometric parameters of the metasurface. Here, we propose to utilize phase change materials to tune the properties of light-emitting metasurfaces designed to support quasi-BIC states in the telecom wavelength range. In our design, a thin layer of a phase change material, which provides strong contrast of refractive index when switched from the amorphous to the crystalline state, is located on top of the resonators made of amorphous silicon (a-Si). Depending on the selected phase change material, we numerically demonstrate different functionalities of the metasurface, In particular, for low-loss Sb2Se3 we evidence spectral tuning effects, whereas for Ge2Sb2Te5, we report an “on”/“off” switching effect of the quasi-BIC resonance. Furthermore, we investigate the influence of the crystallization fraction and the asymmetry parameter of the metasurface on the results. This work provides concrete design blueprints for switchable metasurfaces, offering new opportunities for nanophotonics devices or integrated photonic circuits.
CRIS-Team Scopus Importer:2023-04-20